Near-Infrared Spectroscopic Screening for Bladder Disease in Africa: Training Rural Clinic Staff to Collect Data of Diagnostic Quality - Lynn Stothers; Andrew Macnab; Sharif Mutabazi; Ronald Mukisa; Behnam Molavi; Babak Shadgan (Journal of Spectroscopy)
Background. While near-infrared spectroscopy (NIRS) has recognized relevance for developing countries, biomedical applications are rare. This reflects the cost and complexity of NIRS and the convention of comprehensive training for accurate data collection. In an international initiative using transcutaneous NIRS to screen for bladder disease in Africa, we evaluated if interactive training enabled clinic staff to collect data accurately. Methods. Workshop training in a Ugandan medical clinic on NIRS monitoring theory; bladder physiology and chromophore changes occurring with disease; device orientation; device positioning over the bladder, monitoring subjects during voiding; and saving/uploading data. Participation in patient screening followed with observation, assistance, and then data collection. Evaluation comprised conduct of serial independent screenings with analysis if saved files were of diagnostic quality. Results. 10 individuals attended 1-hour workshops and then 0.5–3.0 hours of screening. Five then felt able to conduct screening independently and all collected data were of diagnostic quality (>5 consecutive patients); all had participated in screening for >1.5 hours (6+ subjects); less participation allowed competent assistance but not consistent adherence to the monitoring protocol. Conclusion. A simplified NIRS system, small-group theory/orientation workshops, and >I.5 hours of 1 : 1 training during screening enabled clinic staff in Africa to collect accurate NIRS data.